PERKAWINAN SATU MARGA (PERKAWINAN ADAT BATAK ANGKOLA DI KECAMATAN SIPIROK KABUPATEN TAPANULI SELATAN SUMATERA UTARA) - Rosita Manalu; Isjoni; Yanuar . (Jurnal Ilmiah Wahana Pendidikan, 2023)
Marriage of the same clan is a marriage carried out by the same clan and is considered a blood marriage from the father’s lineage (patrilineal). As time goes by, this marriage of the same clan has occurred in several places. Along with the development of the times strengthen the occurrence of social change. This social change can occur by the community itself and even people from outside. With increasing public insight, the people’s mindset towards the values ​​of cultural traditions has decreased resulting in deviations from cultural values, one of which is the deviation by the Angkola Batak community regarding marriages of one clan. The aims of this study were 1) to find out the factors that influence Angkola Batak clan marriages in the Sipirok District, South Tapanuli Regency. 2) To find out the impact of one-margin marriage in Sipirok sub-district, South Tapanuli Regency, North Sumatra. 3) To find out the life of the Angkola Batak Indigenous people who carry out clan marriages. The method used in this research is a qualitative research method. This marriage of the same clan occurs because of love and death, hiding the clan, location or environmental factors and religious factors. The impact caused by the marriage of the same clan is to pay sanctions and report to the customary king, not being customary, damaging kinship or rituals, destroying traditional cultural values ​​and breaking up relationships or divorce. As for the lives of perpetrators of marriages from the same clan, at the beginning they receive scorn, which over time will disappear and their lives will be normal and no discrimination will be accepted.